Identify the Risk Factors of COVID-19-Related Acute Kidney Injury: A Single-Center, Retrospective Cohort Study - Wang, Jing; Wang, Zhixian; Zhu, Yunpeng; Li, Haichao; Yuan, Xiaoning; Wang, Xiaoning; Wang, Yuxi; Hu, Jinqian; Feng, Chunxiang; Liu, Chang; Liu, Shiliang; Yu, Kai; et al. (Frontiers in Medicine, 2020)
Background: The kidney is a target organ that could be infected by SARS-CoV-2, and acute kidney injury (AKI) was associated with a higher risk of COVID-19 patients in-hospital death. However, no published works discussed about the risk factors of COVID-19 related AKI. Methods: We conducted a retrospective cohort study, recruiting COVID-19 inpatients from the Sino-French branch of Tongji Hospital. Demographic, clinical, treatment, and laboratory data were collected and compared. We used univariable and multivariable logistic regression methods to identify the risk factors of COVID-19 related AKI. Results: Of the 116 patients in our study, 12(10.3%) were recognized as AKI, including 5(4.3%) in-hospital AKI. Multivariable regression showed increasing odds of COVID-19 related AKI associated with COVID-19 clinical classification (OR=8.155, 95% CI=1.848-35.983, ref=non-critical, p=0.06), procalcitonin more than 0.1 ng/mL (OR=4.822, 95% CI=1.095-21.228, p=0.037), and estimated glomerular filtration rate (eGFR) less than 60 mL/min/1.73m2 (OR=13.451, 95% CI=1.617-111.891, p=0.016). Conclusions: COVID-19 related AKI was likely to be related to multi-organ failure rather than the kidney tropism of the SARS-Cov-2. The potential risk factors of COVID-19 clinical classification, procalcitonin more than 0.1 ng/mL, and eGFR less than 60 mL/min/1.73m2 could help clinicians to identify patients with kidney injury at an early stage